Grüsse von Harald Blauzahn?-Neue Forschungen in der Borgsumburg auf der nordfriesischen Insel Föhr - Hüser, Kirsten; Segschneider, Martin (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
Located about 1 km north the village Borgsum on a moderately raised moraine crest, a circular rampart, visible from afar, still bears witness to the monument preserved above ground. The Borgsumburg on the North Frisian Island Föhr has a height of nearly 8 m and an inner diameter of almost 100 m. Excavations in the 1950s uncovered parts of several well-preserved buildings with sod walls in the inner area, which can be dated to the period from the 9th to the late 10th century. Geomagnetic and -radar surveys in 2001 and 2003 revealed further remains of numerous closely spaced sod buildings along the inside of the circular fortification. Both date and function still raise many questions. Since June 2021, a project funded by the Frederik Paulsen Foundation investigates the interior of the Borgsumburg according to current questions based on archaeological excavations, pedological investigations and botanical analyses. Summerly excavations have revealed many new insights. Excellent preservation conditions led to finds like e. g. textile fragments, bird remains with feathers and eggshells. The youngest of the four settlement phasesdates dendrochronologically to the years of around 980 AD. This is the time of Harald Bluetooth´s Trelleborg fortresses, indicating that there might be some sort of connection, i. e. it seems that the refurbishment of an already existing circular rampart was favoured over building a new one